Highly elastic and self-healing nanostructured gelatin/clay colloidal gels with osteogenic capacity for minimally invasive and customized bone regeneration. (5th January 2023) - Dou, Zhenzhen; Tang, Han; Chen, Kaiwen; Li, Dize; Ying, Qiwei; Mu, Zhixiang; An, Chuanfeng; Shao, Fei; Zhang, Yang; Zhang, Yonggang; Bai, Haoliang; Zheng, Guoshuang; et al.
Abstract: Extrusible biomaterials have recently attracted increasing attention due to the desirable injectability and printability to allow minimally invasive administration and precise construction of tissue mimics. Specifically, self-healing colloidal gels are a novel class of candidate materials as injectables or printable inks considering their fascinating viscoelastic behavior and high degree of freedom on tailoring their compositional and mechanical properties. Herein, we developed a novel class of adaptable and osteogenic composite colloidal gels via electrostatic assembly of gelatin nanoparticles and nanoclay particles. These composite gels exhibited excellent injectability and printability, and remarkable mechanical properties reflected by the maximal elastic modulus reaching ∼150 kPa combined with high self-healing efficiency, outperforming most previously reported self-healing hydrogels. Moreover, the cytocompatibility and the osteogenic capacity of the colloidal gels were demonstrated by inductive culture of MC3T3 cells seeded on the three-dimensional (3D)-printed colloidal scaffolds. Besides, the biocompatibility and biodegradability of the colloidal gels was proved in vivo by subcutaneous implantation of the 3D-printed scaffolds. Furthermore, we investigated the therapeutic capacity of the colloidal gels, either in form of injectable gels or 3D-printed bone substitutes, using rat sinus bone augmentation model or critical-sized cranial defect model. The results confirmed that the composite gels were able to adapt to the local complexity including irregular or customized defect shapes and continuous on-site mechanical stimuli, but also to realize osteointegrity with the surrounding bone tissues and eventually be replaced by newly formed bones.